Amine hardeners and epoxy cross-linker from aromatic renewable resources. (December 2015) - Fache, Maxence; Montérémal, Camille; Boutevin, Bernard; Caillol, Sylvain
Graphical abstract: Highlights: Biobased monomers for epoxy cross-linking were synthesized. New triepoxy monomer was synthesized from vanillin. Furan diamine was synthesized from furan. Epoxy polymers with interesting thermal properties were synthesized thereof. Structure–property relationships were investigated. Abstract: Bio-based epoxy thermosets are currently extensively investigated. To be industrially relevant, bio-based epoxy formulations must be tailored so that the properties of the resulting thermosets can be conveniently controlled. This can be achieved by choosing the right hardener. Amine hardeners were thus synthesized from potentially bio-sourced vanillin and furfural. These compounds are also aromatic, an important structural feature to reach good thermo-mechanical properties. A tri-functional, vanillin-derived epoxy cross-linker was also synthesized. Multi-functional epoxy monomers can increase the cross-linking density of the network, which is another convenient way of controlling the final properties. Epoxy thermosets were prepared from bio-based epoxy monomers and hardeners, as well as from reference compounds commonly used in industry. These polymers were characterized and structure–property relationships are discussed.